Mast cells and tryptase are linked to itch and disease severity in mycosis fungoides: Results of a pilot study - Terhorst-Molawi, Dorothea; Lohse, Katharina; Ginter, Katharina; Puhl, Viktoria; Metz, Martin; Hu, Man; Maurer, Marcus; Altrichter, Sabine (Frontiers in Immunology, 2022)
Introduction: In mycosis fungoides (MF), the most common cutaneous T-cell lymphoma, itch is a frequent clinical symptom. Whether mast cells (MCs), eosinophils (Eos) or their mediators play a role in MF-associated itch or disease severity is controversially discussed. Here, we explored the role of MC and Eo numbers in the skin as well as blood levels of their mediators in disease severity and itch. Methods: In 10 patients with MF and 10 matched control subjects we assessed disease severity, itch, and quality of life impairment using dedicated tools such as the mSWAT, ItchyQoL and DLQI. We analysed skin biopsies and measured serum levels of tryptase, a mast cell mediator, as well as of the eosinophil products eosinophil cationic protein (ECP) and major basic protein (MBP). Results: The presence of chronic itch, in 4 of 10 patients, was associated with significantly higher disease severity (mSwat), larger body surface area affected, and stronger QoL impairment (Itchy-Qol, DLQI). Serum levels of tryptase, but not ECP and MBP, were linked with patient-reported disease severity, body surface area affected, and the presence of itch. 3 of the 4 patients with chronic itch, but none of the 6 patients without, had tryptase levels above >6µg/l. Numbers of MCs in the papillary dermis were higher in MF skin lesions then in non-lesional skin of MF patients and skin of healthy controls. Discussion: The MC-mediator tryptase, in MF, is linked to disease activity and impact, most prominently to itch. Our findings call for larger studies that explore the role of MCs, tryptase and other MC mediators as drivers of itch and their role in MF pathogenesis.